Domain specific association between physical activity and affect in adolescents' daily lives: an ecological momentary assessment study. Issue 3 (4th March 2023) - Bourke, Matthew; Hilland, Toni A.; Craike, Melinda
Abstract: Objective: Little is known about the domain specific associations between moderate-to-vigorous physical activity (MVPA) and affect. This study aimed to determine whether the association between MVPA and affect differed by domain in adolescents. Design: Overall, 119 adolescents (mean age = 14.7 years) provided information about their affective states multiple times a day over a four-day period using ecological momentary assessment (EMA). Additionally, minutes of MVPA were measured using accelerometers and participants self-reported whether they were participating in recreational physical activity, active travel, or household physical activity at the time of an EMA prompt. Main Outcome Measures: The main outcomes that were measured were affective valence, energetic arousal and tense arousal. Results: Participants who engaged in more recreational MVPA on average reported more positive valence, more energetic arousal, and less tense arousal. Additionally, participants reported more energetic arousal when they participated in greater levels of recreational MVPA than usual, but also more tense arousal. Active travel and household physical activity were not associated with valence, energetic arousal or tense arousal. Conclusion: These findings highlight the importance of encouraging participation in recreational physical activities to promote positive affective outcomes.